Community-Institutional Partnerships to Strengthen Maternal Health Care: Case Study of the First Obstetrics and Gynecology Specialty Training Program in Liberia - Beddoe, Ann Marie; Reis, Maureen; Benson, Angela; Rehwaldt, Lise; Mullbah, John; Johnson, Janetta; Lieber, Molly; Dottino, Andrew; Maund, Corrine; Campbell, Sara; Kerry, Vanessa; Solomon, Julie; et al. (Frontiers in Public Health, 2022)
Despite major setbacks to its health infrastructure and health workforce capacity, Liberia began its first post-graduate training program for physicians in 2013. Specialty training in Internal Medicine, Pediatrics, General Surgery and Obstetrics and Gynecology were the four inaugural Residency programs that recruited graduates from the country’s only medical school, A.M. Dogliotti College of Medicine. The Obstetrics and Gynecology residency program was designed to combat the rising maternal mortality and strengthen health systems to improve maternal care. The program adapted in the face of challenges posed by limited financial support, lack of specialist-faculty and general physician shortages and the Ebola virus outbreak. The manuscript discusses the challenges and successes of the program and demonstrates how the shortage of teaching faculty was addressed by developing a collaboration between local government and educational communities, a United States (US) academic institution and volunteers from the Global Health Service Partnership.